Identity and Ambition: North Macedonia’s status seeking through its foreign policy (2006-2017) - Gjeraqina Leka (Academicus International Scientific Journal, 2025)

(untitled)
This paper analyzes North Macedonia’s foreign policy behavior in the period of 2006-2017, evaluating its status seeking endeavors as a small state within international politics. Using a qualitative methodology which builds upon a case study, the paper researches the determinants of small states’ foreign policy, with an emphasis on ambition and capacity. The paper argues that under VMRO DPMNE’S rule, North Macedonia led an identity driven foreign policy, characterized by projects of antiquization, which in turn would cause a latent shift from the country’s traditional Euro-Atlantic orientation. Such overreaching ambition, which aimed to elevate the country’s international standing, clashed with the geopolitical realities, resulting in diplomatic isolation, regional tensions, and domestic instability. The findings underscore the limitations to identity driven foreign policy for small states and stress the importance of harmonizing aspirations with capacity in ensuring sustainable international standing.